Advances in constructing silver nanowire-based conductive pathways for flexible and stretchable electronics. Issue 32 (1st August 2022) - Yang, Yuanhang; Duan, Shun; Zhao, Hong
Abstract : This review surveys up-to-date advances in the development of AgNW-based flexible and stretchable electronics, including fabrication methods, strategies to enhance the conductivity of AgNW network, as well as applications and future perspectives. Abstract : With their soaring technological demand, flexible and stretchable electronics have attracted many researchers' attention for a variety of applications. The challenge which was identified a decade ago and still remains, however, is that the conventional electrodes based on indium tin oxide (ITO) are not suitable for ultra-flexible electronic devices. The main reason is that ITO is brittle and expensive, limiting device performance and application. Thus, it is crucial to develop new materials and processes to construct flexible and stretchable electrodes with superior quality for next-generation soft devices. Herein, various types of conductive nanomaterials as candidates for flexible and stretchable electrodes are briefly reviewed. Among them, silver nanowire (AgNW) is selected as the focus of this review, on account of its excellent conductivity, superior flexibility, high technological maturity, and significant presence in the research community. To fabricate a reliable AgNW-based conductive network for electrodes, different processing technologies are introduced, and the corresponding characteristics are compared and discussed. Furthermore, this review summarizes strategies and the latest progress in enhancing the conductive pathway. Finally, we showcase some exemplary applications and provide some perspectives about the remaining technical challenges for future research.